2017
DOI: 10.21273/horttech03713-17
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Survival of Two Western Milkweed Species: Effects of Container Volume and Fertilizer Rate

Abstract: Diminishing milkweed (Asclepias sp.) populations are contributing to the conspicuous decline of the iconic monarch butterfly (Danaus plexippus). This research sought to improve milkweed propagation success, a core component of summer habitat restoration projects. Specifically, this research assessed the effects of container volume and fertilizer application rate on growth and first year field survival of two species of milkweed common to western Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
4
6
1
Order By: Relevance
“…The findings in this experiment on compost volume are consistent with previous studies (Bernaola‐Paucar et al, 2018; Dominguez‐Lerena et al, 2006; Hanson et al, 2017; Jacobs et al, 2020; Meyer & Cunliffe, 2004; Pinto et al, 2012, 2015). Larger compost volume here provided the seedlings better access to a range of resources: light (both natural and artificial), water, nutrients, and rooting volume.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings in this experiment on compost volume are consistent with previous studies (Bernaola‐Paucar et al, 2018; Dominguez‐Lerena et al, 2006; Hanson et al, 2017; Jacobs et al, 2020; Meyer & Cunliffe, 2004; Pinto et al, 2012, 2015). Larger compost volume here provided the seedlings better access to a range of resources: light (both natural and artificial), water, nutrients, and rooting volume.…”
Section: Discussionsupporting
confidence: 92%
“…The optimal volume will depend on the size the plug plants are grown to (Poorter, Bühler, et al, 2012). Larger volumes increase seedling growth rate and produce seedlings greater in height, stem base diameter, and total biomass (Bernaola-Paucar et al, 2018;Dominguez-Lerena et al, 2006;Hanson et al, 2017;Jacobs et al, 2020;Meyer & Cunliffe, 2004;Pinto et al, 2012Pinto et al, , 2015. Under favorable field conditions, the initial size of transplants does not affect the survival rate (Dominguez-Lerena et al, 2006;Hanson et al, 2017;Pinto et al, 2015;Romero-Munar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased fertilizer rate from low (3.2 gÁL À1 ) to medium (5.3 gÁL À1 ) or low to high (8.5 gÁL À1 ) resulted in 3% or 13% increases in the height of sandhill milkweed after 16 weeks of container production. This result was similar to, but less pronounced than, that reported by Hanson et al (2017), who showed that two western North America native milkweed, showy milkweed [A. speciosa (Torr.)] and narrowleaf milkweed [A. fascicularis (Decne.…”
Section: Discussionsupporting
confidence: 86%
“…Treatments. To test the intergenerational effects of resource quality, we grew host plants at low or high levels of fertilizer, which has been shown to increase plant nitrogen (Awmack & Leather, 2002;Fagan et al, 2002;Slater et al, 2019), height, and biomass in Asclepias species (Hanson et al, 2017). Aphids tend to be limited by nitrogen, and the addition of nitrogen through fertilizer has been shown to benefit aphid fitness (Awmack & Leather, 2002;Fagan et al, 2002;Slater et al, 2019).…”
Section: Experimental Designmentioning
confidence: 99%